Effectiveness of a standard protocol for tranexamic acid administration in total hip and knee arthroplasty – does it make a difference? - Sudhan. S, Ram; Karthick, Srinivas; Nagendra, Vijetha; Asokan, Jithesh; George, Vinod; J, Jacob (Surgical Review: International Journal of Surgery, Trauma and Orthopedics, 2020)
Background: Intraoperative blood loss plays a key role in the outcome of any surgery and is most important during the immediate post-operative period in the management, for both the operating surgeon and the anesthetist. The present study compares postoperative hemoglobin decrease and blood transfusion requirements in total knee and hip arthroplasty with and without standardized perioperative tranexamic acid infusion. Methods: This is a prospective randomized controlled study done on 41 patients undergoing a major joint replacement (total knee and hip arthroplasty) in the south Indian population in a single center. The primary aim of the study was to prove the efficiency of standardized tranexamic acid administration in reducing blood loss and need for blood transfusion in total knee and hip arthroplasty by comparing postoperative hemoglobin levels, peri-operative hemoglobin drop and frequency of blood transfusion in 2 groups one receiving and the other not receiving tranexamic acid during the peri-operative period. Results: The mean pre-operative hemoglobin in the tranexamic acid group was 13.45 and in the control group was 13.0 with a p-value of 0.267, The mean hemoglobin level as on a postoperative day 1 in the tranexamic acid group was 12.32 and in the control group was 10.78 with p-value <0.001. The mean post-op hemoglobin levels on POD 3 in the tranexamic acid group were 11.75 and in Control group was 9.31 with p-value <0.001. The hemoglobin drop in the tranexamic acid group from pre-op to POD 3 was 1.7 mg/dl whereas in the control group the hemoglobin drop from pre-op to Pod 3 was 3.69 mg/dl which was more than double when compared to the tranexamic acid group. Out of 20 patients in the control group 3 patients, one patient who underwent total knee arthroplasty and two patients who underwent Total hip arthroplasty needed 1 unit of blood transfusion postoperatively. Conclusion: The use of standardized Tranexamic acid infusion during the perioperative period of Total Hip and Knee Arthroplasty reduced the perioperative blood loss which was evident by high mean postoperative hemoglobin levels and low mean postoperative hemoglobin drop and decreased need for blood transfusion in Tranexamic acid group when compared to the control group.